Protótipo de rede social para mães atípicas com crianças com Transtorno Espectro Autista - RODRIGUES, Raysa Ramos (2024)
This study presents a prototype of an application aimed at aiding atypical mothers who have difficulty describing Autism Spectrum Disorder (ASD) during their first contact, considering the concept of social networks (online and offline) with fundamental elements of human communication. The prototype was based on the analysis of reports from mothers of autistic children, studies of Jürgen Habermas's communicative actions, Pierre Lévy's studies, informal testimonials collection, and reflections made through observations of interpersonal communication and interactions established in person. The research also aimed to understand the main difficulties faced by atypical mothers when describing ASD during their first contact, seeking to identify the most relevant information to be transmitted and the best way to transmit it. Based on the results obtained, it was possible to develop a prototype of an application that aims to assist mothers during this crucial moment, providing accurate and relevant information about ASD and offering a safe and welcoming environment for sharing experiences and information among mothers. It is expected that the use of this application will contribute to greater understanding and awareness of ASD, reducing stigma and misinformation surrounding the disorder and helping mothers to deal more effectively with the demands of motherhood for autistic children.